Organic contaminants degradation from the S(IV) autoxidation process catalyzed by ferrous-manganous ions: A noticeable Mn(III) oxidation process. (15th April 2018) - Zhang, Jiaming; Ma, Jun; Song, Haoran; Sun, Shaofang; Zhang, Zhongxiang; Yang, Tao
Abstract: Remarkable atrazine degradation in the S(IV) autoxidation process catalyzed by Fe 2+ -Mn 2+ (Fe 2+ /Mn 2+ /sulfite) was demonstrated in this study. Competitive kinetic experiments, alcohol inhibiting methods and electron spin resonance (ESR) experiments proved that sulfur radicals were not the major oxidation species. Mn(III) was demonstrated to be the primary active species in the Fe 2+ /Mn 2+ /sulfite process based on the comparison of oxidation selectivity. Moreover, the inhibiting effect of the Mn(III) hydrolysis and the S(IV) autoxidation in the presence of organic contaminants indicated the existence of three Mn(III) consumption routes in the Fe 2+ /Mn 2+ /sulfite process. The absence of hydroxyl radical and sulfate radical was interpreted by the competitive dynamics method. The oxidation capacity of the Fe 2+ /Mn 2+ /sulfite was independent of the initial pH (4.0–6.0) because the fast decay of S(IV) decreased initial pH below 4.0 rapidly. The rate of ATZ degradation was independent of the dissolved oxygen (DO) because that the major DO consumption process was not the rate determining step during the production of SO5 - . Phosphate and bicarbonate were confirmed to have greater inhibitory effects than other environmental factors because of their strong pH buffering capacity and complexing capacity for Fe 3+ . The proposed acetylation degradation pathway of ATZ showed the application of the Fe 2+ /Mn 2+ /sulfite process in the research of contaminants degradation pathways. This work investigated the characteristics of the Fe 2+ /Mn 2+ /sulfite process in the presence of organic contaminants, which might promote the development of Mn(III) oxidation technology. Graphical abstract: Image 1 Highlights: The addition of Fe 2+ enhanced greatly ATZ degradation compared with Mn 2+ /sulfite. Mn(III) was confirmed to be the major oxidation species rather than sulfur radicals. Three Mn(III) consumption routes existed in the Fe 2+ /Mn 2+ /sulfite process. Single electron transfer existed in the ATZ degradation process during Mn(III) oxidation.